Innovative and Interactive Online English Teaching Methods at 12th Grade Majoring DKV in SMK Buddhi Kota Tangerang - Faisal, Faisal; anggraini, anggraini; Yastanti, Unpris (SCOPE: Journal of English Language Teaching, 2024)
Nowadays, due to the pandemic and other problems, the establishment of physical classes is a big headache for both students and teachers, due to which the education system all over the world is shifted to the online system from the physical system Advance technologies such as the Internet of Things are playing a significant part in various sectors of life such as health, business, and education. The results found in this research are that a teacher who teaches at 12th grade majoring DKV in SMK Buddhi has implemented innovative and interactive teaching methods which include Teacher methods, group discussions, learning by doing, question and answer sessions, think-pair-share, buzz sessions, use of different learning tools than before and experimental learning.